Contributing factors to primary headaches chronicity - M. I. Karpova; Yu. S. Shamurov; A. V. Zuyeva (Бюллетень сибирской медицины)
Comparison of episodic and chronic forms of primary headaches to reveal the possible factors leading to the disease chronicity has been performed. Some of the comorbidities were considered to be the conditions resulting in a more severe course of migraine and headaches of tension. Significant prevalence of clinical manifestations of immune system impairment in patients with chronic cephalgia was noted. It was suggested that the above impairment might be one of the factors accounting for the transformation of course of primary headaches.